Long-term Effects of Hospital Deliveries - Martin Fischer; Martin Karlsson; Nikolaos Prodromidis (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2021)
This paper analyzes the long-term effects on mortality and socio-economic outcomes from institutional delivery. We exploit two Swedish interventions that affected the costs of hospital deliveries and the supply of maternity wards during the 1926–46 period. Using exogenous variation in the supply of maternity wards to instrument the likelihood of institutional delivery, we find that delivery in hospital has substantial effects on later-life outcomes such as education and mortality. We argue that a decrease in child morbidity due to better treatment of complications is a likely mechanism. This interpretation is corroborated by evidence from primary school performance, showing a large reduction in the probability of low performance. In contrast to an immediate and large take-up in hospital deliveries as response to an increase in the supply, we find no increase in hospital births from the abolishment of fees – but some degree of displacement of high-SES parents.
Keywords: I18; I13; N34; 330; Institutional delivery; diffusion of innovations; difference-in-discontinuities